Effects of Herbicides on the Microbial Community and Urease Activity in the Rhizosphere Soil of Maize at Maturity Stage. (22nd April 2021) - Chen, Jie; Yang, Wenping; Li, Jin; Anwar, Sumera; Wang, Kai; Yang, Zhenping; Gao, Zhiqiang
Abstract : Studying the effects of herbicides on microbial community and urease activity in the rhizosphere soil of maize is helpful to clarify the mechanisms herbicides used to affect soil microbial environment. In this research, four common preemergence maize specific herbicides, nicosulfuron+atrazine (A1), alachlor+acetochlor+atrazine (A2), propisochlor+atrazine (A3), and acetochlor+atrazine (A4), were selected to use in a pot trial. A preemergence herbicide nonspecific for maize, dinitraniline (A0), was used as the positive control, whereas water instead of herbicide was considered as the negative control (CK). At the maturity stage, the microbial communities and urease activity in the 0-20 cm, 20-40 cm, and 40-60 cm rhizosphere soils of maize were analyzed. Results showed that A0 dramatically suppressed maize growth, with no grain got finally, while A1 displayed the weakest effect. The tested herbicides affected the microbial community in the 0-20 cm layer greater than in the 20-60 cm ones, with A1 displaying the greatest effect. In the 0-20 cm soil, A1 largely reduced the relative abundance of the top three dominant genera, Prevotella, Barnesiella, and Lactobacillus in the CK soil, by 99.0%, 98.7%, and 79.2%, and made Pseudomonas, Gemmatimonas, and Sphingomonas became the new dominant genera, while A2 and A3 displayed similar but slighter effects. All herbicides dramatically reduced the relative abundance of the top one dominant fungal phylum (Ascomycota) and genus ( Diatrype ) in the CK soil, from 45% to 5.2%-7.9% and 42% to 2.1%-3.2%. A0 dramatically dropped the urease activity in the 0-60 cm soils, by 30.5%-33.1%, whereas A1-A4 displayed an unsignificant effect. In conclusion, A1 is a suitable herbicide for maize. Both the bacterial community and urease activity in the 0-20 cm rhizosphere soil are suitable indices to evaluate the effects of preemergence herbicides on maize growth and soil microbial environment.